A Trend Differential Analysis of Cryptocurrency Growth and Price Performance: Array - Ngwakwe, Collins (Acta Universitatis Danubius. Œconomica, 2022)
Although Cryptocurrency is growing fast in the digital money market, it is nascent, hence its behaviour appears confounding to investors and users. Objective. This paper aims to analyse significant differences and trends between the 2017 and 2021 Bitcoin prices and market capitalisation. Prior work. the paper relies on prior work on cryptocurrency and leans its results on conformability with the efficient market hypothesis. Method. it uses a t-test for mean difference and trend analysis. Data on price and market capitalisation for Bitcoin covered 357 days in 2017 and 357 days in 2021. Findings. at a P value of 0.000001 show that the 2021 Bitcoin price and market capitalisation performance is significantly higher than the 2017 – with over a thousand percent growth in value. In addition, the trend analysis shows that at the earlier stage of Bitcoin, the market is not much efficient and investors can beat the market, but five years after in 2021, the market efficiency has increased. Significance. it provides the cryptocurrency operators, investors, and users with additional investment decision information to determine five years hence regarding when to invest in cryptocurrency for the best profit and minimal loss. It thus provides a digital money case study for university business schools. Value: cryptocurrency may manifest non-compliance to the efficient market hypothesis when the digital money asset is relatively new to the digital money market and may show compliance to the efficient market hypothesis after about five years of maturity in the digital money market. It thus contributes as it has manifested new light to money market hypothesis and literature